Acupuntura em lombalgia crônica: ensaio randomizado em Unidade de Saúde da Família do Sistema Único de Saúde no Amazonas - (:unkn) unknown (Universidade Federal do Amazonas, 2012)
This was a randomized trial conducted in family health unit in the city of Manaus - Amazonas. The study aimed to examine, in the context of primary health care of the family if the Ryodoraku Acupuncture (AR) and Integrated Neuromuscular Acupoint System (SANMI) are effective for treatment of uncomplicated chronic low back pain in the Family Health Unit of SUS in Manaus, Amazonas. The study was prospective, of intervention in the form of randomized clinical trial comparing open with five arms, with two therapeutic groups, RA and SANMI and two control groups, Simulated Acupuncture (AS) and Care Standard (CP) in patients with uncomplicated low back pain, assisted under the primary health care. The primary outcome was the change in score of Roland-Morris score before and after intervention, while secondary outcomes included changes in indices of quality of life (SF-36) and Visual Analog Scale of pain before and after interventions. Patients were assessed by bioelectric Ryodoraku diagnosis and SANMI. The results showed statistically significant change in AR and SANMI groups when compared to the AS and CP groups, in the scores of Disability Questionnaire Roland-Morris - QIRM (p = 0.000), in the Visual Analogue Scale - VAS (p = 0.000 ), in the SANMI (p = 0.000) and in the eight domains of the SF-36 (p = 0.000). The AS was higher than in CP QIRM scores (p = 0.000), VAS (p = 0.000), SANMI (p = 0.001) and in the eight domains of the SF-36 (p = 0.000). The acupuncture was effective for the treatment of uncomplicated lower back pain, reducing pain, disability and improving quality of life. The study revealed a flaw in the standard care of low back pain in primary health care of Manaus.
Keywords: Acupuntura Ryodoraku; Dor lombar - Tratamento; Medicina Tradicional Chinesa; CIÊNCIAS DA SAÚDE: MEDICINA: CLÍNICA MÉDICA: ORTOPEDIA